SUBSTANTIATION OF PRIORITIES OF INCREASING THE INNOVATIVE ACTIVITY OF THE ORGANIZATIONS FOCUSED ON ACHIEVEMENT OF THE COUNTRY'S FOOD SECURITY CRITERIA - Minaeva, Elena; Yazev, Gregory; Ryabova, Taisiya; Gusev, Valerii (Revista Inclusiones, 2020)
The reason for choosing the research topic is the low scientific and technical level of production, a significant proportion of worn-out capital assets, the lack of modern principles of innovative development of agro-industrial complex enterprises. The problem is posed by the search for economic opportunities to increase the innovative level of the enterprises based on the motivation for creating new types of equipment and technologies. The importance of the problem posed is conditioned by the aggregate interest of consumers in the quality of food, the economic accessibility of competitive domestic products, the reduction of budgetary funds for the purchase of imported goods, the savings from which can be aimed at increasing the innovation level and reducing the labour intensity of technological operations. The purpose of this research is to find grounds for the economic impact of innovation activities on the manifestation of positive trends in the growth of production of agro-industrial complex products, primarily milk and meat, contributing to a reduction in imports. The research focuses on raising human capital, the dominant of which is intellectual potential, focused on the search and implementation of new ideas. Based on the above-mentioned premise, the relevance of the research topic is conditioned by the need to identify a set of economic priorities for innovation-level growth, aimed at increasing the production of domestic food products and achieving the criteria for food independence. From the point of theory and practice, the obtained results of the research may contribute to the renewal of the principles of innovation activity development, to fulfil the problems in the field of education and to promote the growth of the enterprises efficiency through the implementation of proposals.